Análise das Práticas em Responsabilidade Socioambiental de 40 Empresas Cotadas Pelo Índice Ibovespa a Partir dos Websites e dos Relatórios de Sustentabilidade - Hubert Drouvot (Universidade Regional do Noroeste do Estado do Rio Grande do Sul, 2014)
In response to stakeholders (customers, investors, media) companies are expanding disclosures about their environmental policies. This research aims to analyze the information disclosed on the theme of social responsibility (CSR) 40 companies that have quotes on the Sao Paulo Exchange (Bovespa Index). With a content analysis of the website and annual sustainability reports , the study proposes to identify the frequency of practices in relation to interest groups and the different types of services (in the field of education, culture, health), the whether the practice of philanthropy are used by companies as a complement to their shares in the responsibility chain focused business , to assess the value of spending on CSR in relation to net revenue of the organizations and whether the variable “industry sectors “and” net revenues” have an influence on the characteristics of CSR policies. We observed the presence of duality instrumental vision–normative view, and 60% of companies surveyed practice, while utilitarian’s actions within the chain of business and philanthropic actions. Compared with research indicating that the volume and content of environmental disclosures depend on the size of the companies we found a non-significant trend of the influence of net income of companies on some CSR practices. Regarding the sectors of activity in the sector is Business to Business that practices philanthropy for the communities are the most frequent. Also in this sector of activity that the proportion of companies that disclose their financial data is higher.